Penanaman Nilai Keimanan Dalam Pembelajaran Berbasis Film Nussa dan Rara di Sekolah Dasar - Tresna Qurotul Aeni (IKIP Siliwangi, 2021)
The development of the current era, makes parents feel anxious about the behavior of their children. Most children now prefer the world of gadgets from traditional games. Therefore, parents as the main supervisors in children's first education must be able to choose a content that contains the world of education and instill character values if parents are able to provide technology to children, such as a how-to film and education. This study aims to analyze Learning Planning based on Nussa and Rara Films at SDN 1 Gunung Pereng 1 Tasikmalaya City, to analyze Learning Implementation, to analyze Learning Evaluation based on Nussa and Rara Films at SDN 1 Gunung Pereng 1 Tasikmalaya City. The research method used is descriptive method with a qualitative approach. The sample in this study were 6 grade 2 students. The results showed that the animated film Nussa in this study contained many lessons, advice and life values. The values consist of the characters found in the fifth episode above from 8 values, namely: Religious, disciplined, hard work, independent, friendly/communicative, tolerance, knowledge and responsibility. The assessment categories in this study that have the most are the cultivation of friendly/communicative values and curiosity.